2010
DOI: 10.1074/jbc.m110.170167
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Yeast Telomere Nucleoprotein Core

Abstract: At the core of Saccharomyces cerevisiae telomeres is an array of tandem telomeric DNA repeats bound site-specifically by multiple Rap1 molecules. There, Rap1 orchestrates the binding of additional telomere-associated proteins and negatively regulates both telomere fusion and length homeostasis. Using electron microscopy, viscosity, and light scattering measurements, we show that purified Rap1 is a monomer in solution that adopts a ringlike or C shape with a central cavity. Rap1 could orchestrate telomere funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…The Myb-like domains are positioned in tandem on the DNA, and the N and C termini are located close together so that the DNA is completely enclosed within the protein. This is corroborated by transmission electron microscopy where Rap1 is imaged as a ring-or C-shaped structure (4). In this way, the Rap1 protein efficiently wraps and protects the length of the telomeric DNA and also supplies the platform for the formation of the higher order structure by its C-terminal interaction with the Sir3 and Sir4 proteins (7).…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…The Myb-like domains are positioned in tandem on the DNA, and the N and C termini are located close together so that the DNA is completely enclosed within the protein. This is corroborated by transmission electron microscopy where Rap1 is imaged as a ring-or C-shaped structure (4). In this way, the Rap1 protein efficiently wraps and protects the length of the telomeric DNA and also supplies the platform for the formation of the higher order structure by its C-terminal interaction with the Sir3 and Sir4 proteins (7).…”
mentioning
confidence: 51%
“…Rap1 executes a negative regulation of telomere length via its interacting partners Rif1 and Rif2 in a "protein counting" mechanism, where a higher amount of bound Rap1-Rif complexes will inhibit the telomere extension (2,3). Rap1 binds as a monomer along the length of the telomeric sequence with an average spacing of ϳ18 base pairs (4,5). The crystal structure of the Rap1-DBD in complex with a telomeric DNA sequence revealed that the DNA-binding domain (DBD) 2 of Rap1 is formed by two similar subdomains, which are structurally related to the Myb DNA-binding motifs and the homeodomains (6).…”
mentioning
confidence: 99%
“…More recently, work from Williams et al . (33) showed that indeed the predicted number of Rap1 molecules can be observed both with synthetic telomeric arrays and natural sequences. However, these assays were performed under conditions where the number of protein molecules never exceeded the number of potential canonical Rap1 sites (33).…”
Section: Discussionmentioning
confidence: 92%
“…(33) showed that indeed the predicted number of Rap1 molecules can be observed both with synthetic telomeric arrays and natural sequences. However, these assays were performed under conditions where the number of protein molecules never exceeded the number of potential canonical Rap1 sites (33). Analysis of telomeric sequences in Figure 1a to include all possible Rap1 recognition sites shows that although the 3 bp and 1 bp spacing between the ACACC direct repeats are dominant, a substantial fraction of potential sites contains zero bp spacing, and an even larger fraction contains of a single hemi-site.…”
Section: Discussionmentioning
confidence: 93%
“…The maximal accumulation of Rap1 at telomeres occurs in S/G2 phase. The degree of telomere saturation by Rap1 molecules has an inverse correlation with telomere length (Williams, Levy et al 2010).…”
Section: Telomere Binding Proteinsmentioning
confidence: 98%